(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
Interaction between neoliberal economy and medical biotechnologies brought about a new formulation of the connection between feminine generative potential and value production. In this context it is increasingly difficult to use the traditional tools of biolaw to cope with the problems that biocapital has raised. With a focus on surrogacy, the essay addresses two issues that need to be investigated and rethought in this new scenario: the exploitation/commodification of the human biological material and the safeguard and extension of reproductive self-determination.